Massage's effect on injury, recovery, and performance: A review of techniques and treatment parameters - Standley, R.; Miller, M.; Binkley, H. (Strength and Conditioning Journal, 2010)
IT IS IMPERATIVE THAT THE STRENGTH AND CONDITIONING SPECIALISTS NOT ONLY KNOW THE TYPES OF MASSAGE TECHNIQUES AND THE PHYSIOLOGICAL BENEFITS USED FOR IMPROVING FLEXIBILITY AND PERFORMANCE BUT ALSO KNOW HOW MASSAGE CAN BE USED FOR MUSCLE RECOVERY AND REHABILITATION OF INJURIES WITHIN THE ATHLETIC POPULATION.